Pengaruh Metode Drill dalam Supervisi Klinis terhadap Spiritual Care Perawat - Nunung Rachmawati; Luky Dwiantoro; Bambang Edi Warsito (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
The holistic nursing service is based on the concept that humans are sick not only physically that cured by drug delivery, but also pay attention to other aspects of mental where the patient needs motivation and spirit to cope with illness, social where the patient wants to meet and gather with family/friends and spiritual where the patient wants to pray and pray for healing. Spiritual care is an important part of the overall care provided to improve the quality of life of patients. The role of nurses is now more involved on treatment measures. Proper methods in clinical supervision are necessary for the implementation of spiritual care to be as important as physical care, one of them using drill method. This study aims to analyze the influence of drill methods in the team leader's clinical supervision on the implementation of nurses spiritual care. The research method used is quasy experiment with pretest-posttest research design with control group design. The population of nurse research in inpatient room of PKU Muhammadiyah Yogyakarta and PKU Muhammadiyah Gamping Hospital. A total of 32 nurses were taken as samples through consecutive sampling technique. To see the implementation of spiritual care used observation sheet refers to the label Nursing Interventions Classification, spiritual care is observed before and after the application of drill methods in clinical supervision. Data were analyzed by paired t-test. The results showed the average of nurses' spiritual care before the drill method applied to the intervention group was 6,56 and 6,13 in the control group, after drill method applied in the intervention group was 17,44 and 6,50 in the control group. The results of statistical tests showed that there was a significant difference in nurse's spiritual care before and after the application of drill methods in the intervention group. It is recommended for the hospital to improve the implementation of clinical supervision to the nurses related to non-physical skills using drill method.